Studi Komparasi Tingkat Konsumsi Masyarakat Melalui E-Commerce Sebelum dan Sesudah Masa Pandemi Covid-19 - Fema, Christa Ananda; Rakhmad, Nandita; Bonda, Putri Yasmin E Eberthon; Ramli, Diki; Maulana, Agus (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
The Covid-19 pandemic has had a significant impact on the Indonesian economy, especially e-commerce. The use of e-commerce has increased, causing public consumption to also increase compared to before the pandemic. This study aims to determine the level of public consumption through e-commerce before and after the Covid-19 pandemic. The object of this research is UPN Veteran Jakarta students and several people who use e-commerce. This type of research is quantitative research with instruments in the form of online questionnaires, as well as descriptive quantitative data analysis techniques. The results show that the level of public consumption through e-commerce has increased after the Covid-19 pandemic. People believe in the system, they also claim that the costs incurred through e-commerce are relatively cheap compared to shopping in person.